Modelling the behaviour of the spot prices of various types of coffee (1998)
This paper investigates long-run relationships among the spot prices of four coffee types. We find two cointegrating vectors: one between the prices of Other Milds and Colombian coffee, and the other one between Unwashed Arabicas and Robustas. Following Pesaran and Shin (1996), persistence profile analysis of the two cointegrating vectors shows a rapid adjustment towards their equilibrium value. This suggests that the four coffee markets are highly related, and that discrepancies in the equilibrium relationships are short-lived. Out of sample evaluation of the model is reasonably good, except for two occasions of sharp price increases following adverse weather conditions.